Fluid-structure interaction of computational aerodynamics analysis in paravalvular leakage of transcatheter aortic valve implantation patient - Basri, Adi Azriff (2017)
Fluid Structure Interaction (FSI) is widely known as superior simulation technique that provide significant outcomes through the interaction between fluid dynamic and structure mechanics. In this research, the computational aerodynamic analysis of FSI is carried out to investigate of behavior of human blood flow and aortic wall response associated to heart valve replacement known as Transcatheter Aortic Valve Implantation (TAVI). Even though TAVI has huge potential in providing better solution, yet a lot of complications has occurred such as the effect of hemodynamic forces on the TAVI, the problem of migration associated with the implanted valve and paravalvular leakage (PVL) have to be addressed. Up-to-date, none of the researcher investigated the flow pattern of PVL after implantation of TAVI valve using FSI. The proposed research consists of MRI-Cardiac work, computational and numerical work, as well as experimental. This study has been approved by Institut Jantung Negara (IJN) and have received preliminary CT-scan data, thus the patient case data can be obtained. PVL is highlighted as one of the major complications for the post-TAVI due to possibility of calcification development. Hence, the computational of FSI is carried out, by which the simulation is based on the opening of TAVI valve represented as calcification. In addition, further study is conducted by determining the severity of PVL due to the undersizing of TAVI valve. The experimental study is carried out to validate the simulation model and result analysis representing the real world perspective. The results proven that the presence of PVL disturb the norm of blood flow distribution and aorta structure behaviour. In fact, the opening of 20% GOA (geometric orifice area) of TAVI 26 on human aorta proven the significant impact with highest value of velocity 2.74 times higher and displacement of 1.19 times higher than 100% GOA, thus graded as severe PVL. In addition, the undersizing TAVI valve showed that TAVI 23 has higher possibility of valve migration with 55.01% leakage compared to TAVI 26. Hence, this research provides a noteworthy benchmark with the aid of FSI to predict significant impact of PVL complication for TAVI patient. The outcomes of this study also can be practiced to help the medical practitioner to reducing the risk of re-operation, hence lead to the time saving of the standardization of the computational analysis.